AN OVERVIEW OF HIGH IMPACT LAW JOURNALS IN ASIAN COUNTRIES (UUM Journal of Legal Studies, 2021)
Academic research journals play a significant role in the field of academia. Its major functions in producing, disseminating and exchanging academic knowledge are important to showcase the research performance of individuals. Publication of academic papers has been considered as a criteria for appointments, hiring, promotions and tenure decisions, worldwide. The current requirement to consider publishing in high quality journals is in its indication of the quality of a person’s research output. It is measured through the quality of the academic research publications, the number of citations of specific papers and the total number of citations. Accordingly, it is important to examine the issues regarding high impact publication of Scopus law journals in Asian countries. This is to enable all new SCOPUS law journals to study and practice good governance in publishing quality articles and for the board of editors to enhance the quality of journal management. The objectives of this paper are: (i) to examine the profiles of law journals in Asian countries indexed by Scopus and Web of Science (WoS); (ii) to examine citations and impact factors of law journals in Asian countries indexed by Scopus and WoS; and (iii) to study the ranking of Scopus law journals in Asian countries. This was an exploratory research and thus qualitative research method was adopted. An oline survey and an interview(s) were conducted by the researcher to gather data. The chief editor and managing editors of the Scopus law journals were the respondents via the online survey and an interview was conducted with the expert in managing high impact publications i.e. the Director of Citation and Infometrics Division, Ministry of Education, Malaysia. Besides, secondary data was gathered from Scopus and WoS. In brief, the challenges in managing high impact journals are securing and maintaining high quality articles published by the journals. There must be periodic review of standard operating procedures by the board of editors in order to maintain an effective and efficient reviewing process, together with engaging staff with excellent proofreading skills. Additionally, the publisher must continuously upgrade the online publication system and maintain a friendly website for authors, subscribers and readers. Ethical practices and a focus on high quality and standard of article publication must be upheld by writers, editors, publishers including the indexing body.